Purification and Properties of an Enzyme Capable of Degrading the Sheath of Sphaerotilus natans - Takeda, Minoru (American Society for Microbiology, 2000)
Microorganisms which can degrade and grow on the purified sheath of a sheathed bacterium Sphaerotilus natans were collected from soil and river water. Two bacterial strains were isolated from the soil and designated strains TB and TK. Both strains are rod shaped, negatively stained by gram staining, facultatively anaerobic, and formed ellipsoidal endospores. These characteristics suggested that the isolates belong to the genus Paenibacillus, according to Ash et al. (C. Ash, F. G. Priest, and M. D. Collins, Antonie Leeuwenhoek 64:253–260, 1993). Phylogenetic analysis based on the 16S rDNA supported this possibility. Purification of the sheath-degrading enzyme was carried out from the culture broth of strain TB. The molecular weight of the enzyme was calculated to be 78,000 and 50,000 by sodium dodecyl sulfate-polyacrylamide electrophoresis and gel filtration chromatography, respectively. Enzyme activity was optimized at pH 6.5 to 7.0 and 30 to 40°C. The reaction was accelerated by the addition of Mg(2+), Ca(2+), Fe(3+), and iodoacetamide, whereas it was inhibited by the addition of Cu(2+), Mn(2+), and dithiothreitol. The enzyme acted on the polysaccharide moiety of the sheath, producing an oligosaccharide the size of which was between the sizes of maltopentaose and maltohexaose. As the reaction proceeded, the absorbance at 235 nm of the reaction mixture increased, suggesting the generation of unsaturated sugars. Incorporation of unsaturated sugars was also suggested by the thiobarbituric acid reaction. It is possible that the enzyme is not a hydrolytic enzyme but a kind of polysaccharide eliminase which acts on the basic polysaccharide.